GPS Cycle Slip Detection Considering Satellite Geometry Based on TDCP/INS Integrated Navigation - Younsil Kim; Junesol Song; Changdon Kee; Byungwoon Park (Sensors, 2015)
This paper presents a means of carrier phase cycle slip detection for an inertial-aided global positioning system (GPS), which is based on consideration of the satellite geometry. An integrated navigation solution incorporating a tightly coupled time differenced carrier phase (TDCP) and inertial navigation system (INS) is used to detect cycle slips. Cycle-slips are detected by comparing the satellite-difference (SD) and time-difference (TD) carrier phase measurements obtained from the GPS satellites with the range estimated by the integrated navigation solution. Additionally the satellite geometry information effectively improves the range estimation performance without a hardware upgrade. And the covariance obtained from the TDCP/INS filter is used to compute the threshold for determining cycle slip occurrence. A simulation and the results of a vehicle-based experiment verify the cycle slip detection performance of the proposed algorithm.